Effects of variety reduction and amplification in circular feedback systems. Issue 9 (3rd November 2014) - Fischer, Thomas
Abstract : Purpose: – The purpose of this paper is to present the result of an experiment examining the effects of changing input and output channel variety in an optical feedback system and their potential to give rise to novelty, as some non-trivial systems do. Design/methodology/approach: – The experimental design is based on a digital computer connected to a digital photo camera (input channel), and to a monitor screen (output channel). The camera is pointed at the monitor to form a circular feedback system. Monitor and camera resolutions constitute the variable input and output variety of the system, allowing the visual investigation of effects of variety reduction and variety amplification in circular feedback systems. Findings: – Results suggest that variety amplification in input and/or output channels promotes the emergence of discernible novelty in the apparent absence of a creative/generative capability or agenda within the recursive system. Research limitations/implications: – An analogy between an optical feedback system and human novelty generation is shown, while generalisability of observations made beyond the described experiment remains to be established. Originality/value: – A new approach to the computational modelling of aspects of human creativity is presented. Photographic investigation of variety reduction and variety amplification is new, and hoped to be of value to those wishing to examine these theoretical concepts in concrete terms.